Analysis Of The Effectiveness Of A Spiritual-Based Transformational Leadership Workshop In Enhancing Head Nurses' Capacity For Patient Safety At Hospitals In Central Sulawesi - Kolomboy, Fajrillah; Sipatu, Lindanur; Rizkaningsih, Rizkaningsih; Syamsu, Andi Fatmawati; Jun Cen, Hana W. (Politeknik Kesehatan Kemenkes Mamuju, 2025)
Patient safety is a global health problem and is a very complex health issue that involves many parties. Factors that influence the increase in unsafe patient incidents in hospitals include a weak patient safety culture. Indifference to patient safety causes harm to patients and hospitals. In order to overcome this, the role of leaders as key figures is needed to foster a patient safety culture. With transformational leadership, it is hoped that people will be able to demonstrate a visionary attitude and have the ability to convince others to make changes, prioritize common interests, and motivate other people or groups to achieve goals. To determine the knowledge and skills of all Heads of the Room in implementing a spiritual-based transformational leadership model before and after the workshop. This study used a quasi-experimental method, namely a pre-test and post-test, with a population of 72 ward heads in type B hospitals throughout Central Sulawesi. The number of samples in this study was 40 people, and the results were obtained using the accidental sampling formula. This study was conducted from January to September 2024 in type B hospitals throughout Central Sulawesi. Data analysis was performed using the Wilcoxon test, which showed an increase in scores on the knowledge and skills variables before and after the workshop, with an average of 20.50, with a significance value of p-value for both knowledge and skills variables of 0.000 <0.05.. There is an influence of the workshop on increasing the knowledge and skills of the Head of the Room in implementing the spiritual-based transformational leadership model before and after the workshop. to obtain more complex results, further research needs to be conducted using the Focus Group Discussion (FGD) method..